Odpowiedzi

2010-04-14T19:39:16+02:00
4a-5b-12
-14x-2y-z
6+3x-4z-12a
-6a-5m-3x-12½
-9+5c-2a+2b

Nie jestem pewny
2010-04-14T19:39:34+02:00
4a+(-5b)+(-12)= 4a -5b-12
(-14x)+(-2y)+(-z)=-14x-2y-z
6+3x+(-4z)+(-12a)=6+3x-4z-12a
-6a)+(-5m)+(-3x)+(-12½)=-6a-5m-3x-12i jedna druga
(-9)+5c+(-2a)+2b= -9c+5c-2a+2b
  • Użytkownik Zadane
2010-04-14T19:39:36+02:00
4a+(-5b)+(-12)=4a-5b-12
(-14x)+(-2y)+(-z)=-14x-2y-z
6+3x+(-4z)+(-12a)=6+3x-4z-12a
(-6a)+(-5m)+(-3x)+(-12½)=-6a-5m-3x-12½
(-9)+5c+(-2a)+2b= -9+5c-2a+2b